Synergistic Relationship Between Computational and Mathematical Thinking: The Role of Spreadsheets - Ghosh, Jonaki B (Voices of Teachers and Teacher Educators, 2024)
There is widespread acknowledgement that computational thinking needs to be integrated in the school curriculum. Mathematical thinking (MT) and computational thinking (CT) are mutually supportive and yet distinct. Mathematics as a fundamental school subject therefore becomes the likely choice for integrating CT practices. However, the nature of tasks that integrate MT and CT remains elusive. This paper presents an exemplar from a larger study, where fractal explorations and simulation of problems in probability enabled by spreadsheets led pre-service teachers to develop mathematical concepts and also engage with CT practices. The tasks enabled the participants to engage in processes of visualization, generalization, recursion, iteration, and analysing algorithms, which are important from computational and mathematical standpoints. The evidence of student learning indicates a compelling argument for incorporating such tasks in foundational mathematics courses in pre-service teacher education programmes.